ANALYSIS OF THE EFFECT OF CAPITAL STRUCTURE, COMPANY SIZE AND AGENCY COST ON COMPANY PERFORMANCE - Mohammad Putra Perdana; Moh.Yudi Mahadianto (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of capital structure, firm size, and agency cost on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. The research employs a quantitative approach using secondary data obtained from annual financial reports published by the IDX. The sampling technique applied is purposive sampling, resulting in a selected sample that meets the research criteria. Data analysis is conducted using panel data regression to examine both partial and simultaneous effects of the independent variables on financial performance. The results indicate that capital structure does not have a significant effect on financial performance (P>0.05). In contrast, firm size and agency cost show a significant effect on financial performance (P<0.05), suggesting that larger firms and efficient management of agency costs contribute to better financial outcomes. These findings provide important implications for company management and investors in making strategic financial decisions.